Transnationalism and imperialism : endurance of the global Western film - Mayer, Hervé, 1986-; Roche, David, 1976- (New directions in national cinemas., 2022)
This book redefines American productions of the Western genre as an expression of a transnational ideology and culture of imperialism. Reviewers agree that this collection offers the most impressive sampling of the vast number of global Westerns produced from the silent era to the present day, compared to other publications in recent years on the Western.